2021
DOI: 10.3390/ijms22179225
|View full text |Cite
|
Sign up to set email alerts
|

Low Doses of Ketamine and Melatonin in Combination Produce Additive Antidepressant-like Effects in Mice

Abstract: Major depressive disorder is a disabling disease with the number of affected individuals increasing each year. Current antidepressant treatments take between three to six weeks to be effective with forty percent of patients being resistant to treatment, making it necessary to search for new antidepressant treatments. Ketamine, a phencyclidine hydrochloride derivative, given intravenously, induces a rapid antidepressant effect in humans. In mice, it causes increased neurogenesis and antidepressant-like effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Evidence from nuclear magnetic resonance-based studies and ligand-binding assays have shown that MEL can bind to Ca 2+ -CaM [ 10 , 16 , 17 ]. Exogenous MEL antidepressant-like effects in mice have been recently described [ 25 , 26 ], and modulation of neuroplasticity may underlie this effect. CaMKII plays a key role in neurogenesis and dendritogenesis which are processes stimulated by antidepressants and MEL [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from nuclear magnetic resonance-based studies and ligand-binding assays have shown that MEL can bind to Ca 2+ -CaM [ 10 , 16 , 17 ]. Exogenous MEL antidepressant-like effects in mice have been recently described [ 25 , 26 ], and modulation of neuroplasticity may underlie this effect. CaMKII plays a key role in neurogenesis and dendritogenesis which are processes stimulated by antidepressants and MEL [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Administration of MEL (16 mg/kg) was assessed by a three times dose injection of the VEH or MEL. First injection was administered 24 h before the sacrifice, and the second and third injections were administered 11 h and 30 min [ 26 ] before the anesthesia administration. Mice were perfused with paraformaldehyde 2% with CaCl 2 0.02%, and finally embedded in sucrose for cryopreservation [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The precise physiological meaning of high levels of MEL in the CNS is not known, but presumably, it is to protect neurons and glia from oxidative stress and inflammation, as well as to stimulate the formation of new neurons in specific niches [ 5 ]. In addition, MEL in the CNS has antidepressant-like effects, associated with neurogenesis and dendritogenesis produced in the dentate gyrus of the hippocampus of rodents [ 6 , 7 , 8 ]. Similar effects have been demonstrated for ISSR antidepressants in animal models and postulated as a therapeutic mechanism in humans [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MEL in the CNS has antidepressant-like effects, associated with neurogenesis and dendritogenesis produced in the dentate gyrus of the hippocampus of rodents [ 6 , 7 , 8 ]. Similar effects have been demonstrated for ISSR antidepressants in animal models and postulated as a therapeutic mechanism in humans [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation